Spink2 modulates apoptotic susceptibility and is a candidate gene in the Rgcs1 QTL that affects retinal ganglion cell death after optic nerve damage. - Joel A Dietz; Margaret E Maes; Shuang Huang; Brian S Yandell; Cassandra L Schlamp; Angela D Montgomery; R Rand Allingham; Michael A Hauser; Robert W Nickells (PLoS ONE)
The Rgcs1 quantitative trait locus, on mouse chromosome 5, influences susceptibility of retinal ganglion cells to acute damage of the optic nerve. Normally resistant mice (DBA/2J) congenic for the susceptible allele from BALB/cByJ mice exhibit susceptibility to ganglion cells, not only in acute optic nerve crush, but also to chronic inherited glaucoma that is characteristic of the DBA/2J strain as they age. SNP mapping of this QTL has narrowed the region of interest to 1 Mb. In this region, a single gene (Spink2) is the most likely candidate for this effect. Spink2 is expressed in retinal ganglion cells and is increased after optic nerve damage. This gene is also polymorphic between resistant and susceptible strains, containing a single conserved amino acid change (threonine to serine) and a 220 bp deletion in intron 1 that may quantitatively alter endogenous expression levels between strains. Overexpression of the different variants of Spink2 in D407 tissue culture cells also increases their susceptibility to the apoptosis-inducing agent staurosporine in a manner consistent with the differential susceptibility between the DBA/2J and BALB/cByJ strains.